Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Konsumen pada Usaha Keripik Ribka Sibolga - Alirama Tafonao; Mhd. Shafwan Koto; Heriyawan Hutagalung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of product quality and price on consumer purchasing decisions at Ribka Chips Business in Sibolga. The research method used is quantitative with a descriptive approach. The sample consists of 72 respondents who are consumers of Ribka Chips Business, and data were collected through questionnaires. The results show that the coefficient of determination is 0.606, indicating that 60.6% of the variation in consumer purchasing decisions is jointly influenced by product quality and price, while the remaining 39.4% is influenced by other variables not examined in this study. The t-test results indicate that product quality (t = 4.853; sig = 0.001 < 0.05) and price (t = 2.756; sig = 0.007 < 0.05) have a positive and significant effect on consumer purchasing decisions. Furthermore, the F-test results show that product quality and price simultaneously have a positive and significant effect on consumer purchasing decisions (F = 52.993; sig = 0.001 < 0.05).